A MYB-related transcription factor from peanut, AhMYB30, improves freezing and salt stress tolerance in transgenic Arabidopsis through both DREB/CBF and ABA-signaling pathways - Na Chen; Lijuan Pan; Zhen Yang; Maowen Su; Jing Xu; Xiao Jiang; Xiangzhen Yin; Tong Wang; Feifei Wan; Xiaoyuan Chi (Frontiers in Plant Science, 2023)
Abiotic stresses such as salinity and low temperature have serious impact on peanut growth and yield. The present work investigated the function of a MYB-related transcription factor gene AhMYB30 obtained from peanut under salt and low temperature stresses by transgenic methods. The results indicated that the overexpression of AhMYB30 in Arabidopsis could enhance the resistance of transgenic plants to freezing and salt stresses. The expression of stress-response genes RD29A (Response-to-Dehydration 29A), COR15A (Cold-Regulated 15A), KIN1 (Kinesin 1) and ABI2 (Abscisic acid Insensitive 2) increased in transgenic plants compared with in wild-type. Subcellular localization and transcriptional autoactivation validation demonstrated that AhMYB30 has essential features of transcription factors. Therefore, AhMYB30 may increase salt and freezing stress tolerance as the transcription factor (TF) in Arabidopsis through both DREB/CBF and ABA-signaling pathways. Our results lay the theoretical foundation for exploring stress resistance mechanisms of peanut and offering novel genetic resources for molecular breeding.